PENGENALAN BAHASA INGGRIS SEBAGAI UPAYA PENINGKATAN LITERASI BAGI SISWA SEKOLAH DASAR - Prisiani, Yuri; Faithtria, Monica Glory; Gumay, Fhilia Anasty; Santoso, Salim; Kacen; Dhananjaya, Asoka; Perdana, Novario Jaya (Jurnal Serina Abdimas, 2024)
Education at the primary or elementary school level has an important role in forming the foundation of students' knowledge for use in subsequent education. Therefore, English is the international language most widely used in the world as a medium of communication, technology, business and education with other countries. The aim of this activity is to provide knowledge and skills in using English to state elementary school students C in Cianjur Regency. This activity was chosen because students' ability to speak English and write in English is still lacking due to limited vocabulary and low understanding of the structure of English. The application of English since elementary school is very important to help students remain confident in using a foreign language. The activity method used was qualitative with respondents from grades one to six. Next, learning takes the form of theoretical explanations regarding the structure of English and practice speaking using English. During the learning process, interesting image and video media are used to increase students' motivation. The results of this activity have a positive impact on students. The application of fun and effective English learning is an attraction to increase students' interest in foreign languages ​​as well as to increase self-confidence and open up more educational opportunities in the future. ABSTRAK Pendidikan di tingkat dasar atau sekolah dasar memiliki peran penting dalam membentuk fondasi pengetahuan siswa untuk digunakan pada pendidikan selanjutnya. Oleh karena itu, Bahasa inggris merupakan bahasa internasional yang paling banyak digunakan oleh dunia sehingga sebagai media komunikasi, teknologi, bisnis, dan pendidikan dengan negara lainnya. Tujuan dari kegiatan ini adalah untuk memberikan pengetahuan dan keterampilan dalam penggunaan bahasa inggris kepada siswa sekolah dasar negeri C di Kabupaten Cianjur. Kegiatan ini dipilih karena kemampuan siswa berbicara bahasa inggris dan tulis dalam bahasa inggris masih kurang yang disebabkan oleh keterbatasan kosa kata dan kurangnya pemahaman terhadap struktur Bahasa Inggris. Penerapan bahasa inggris sejak sekolah dasar sangat penting untuk membantu siswa tetap percaya diri dalam menggunakan bahasa asing. Metode kegiatan yang digunakan yaitu kualitatif dengan responden siswa kelas satu sampai enam. Selanjutnya dengan pembelajaran berupa pemaparan teori mengenai struktur Bahasa Inggris dan praktik berbicara menggunakan Bahasa Inggris. Selama proses pembelajaran, digunakan media gambar dan video yang menarik untuk meningkatkan motivasi para siswa. Hasil dari kegiatan ini memberikan dampak positif bagi siswa. Penerapan pembelajaran bahasa inggris yang menyenangkan dan efektif merupakan daya tarik untuk meningkatkan minat siswa dengan bahasa asing serta untuk meningkat kepercayaan diri dan membuka lebih banyak peluang pendidikan di masa depan